Tenets of Specimen Management in Diagnostic Microbiology - Kasarla, Rajeshwar Reddy; Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2023)
The interpretation of microbiological results depends, to a large extent, on the quality of the samples received for investigations. Even with the advancements in laboratory automation and integration of molecular diagnosis in microbiology, interpretation of results still depends on the quality of specimens received. Therefore, an appropriate management of the samples is necessary to achieve an optimal diagnosis in microbiology laboratory. Recently, clinical microbiologists have begun to promote specimen management as a process critical to diagnostic success. Microbiology laboratory results that are accurate, signiﬁcant and clinically relevant depend almost entirely on specimen management process. This article review the specimen management process, special skills and precise concepts required to collect the specimens for effective methods in diagnosis.